Self esteem and social comparison among friends and non friends. - Villareal, Mataji T.
Differences in self esteem of the subjects were examined after exposure to upward and downward comparison processes with either of the subjects friends or non friends. Fifty high school friends were subjected to a social comaprison process. This study was a randomized 2 (upward vs. downward) x2 (friend vs. non friend) factorial design. The independent variables in this study were social comparison (upward vs. downward) and friendship (friend vs. non friend). The dependent variable was self esteem. There were four conditions in the study, namely (1)upward- friends, (2)upward-non friends, (3) downward-friends and (4)downwaard-non friends. Pairs of friends and non-friends together were given feedback after having been asked to do a reporting task. In a pair, one of them was given a positive feedback while the other one was given a negative feedback. The negative feedback included remarks that said she did very poorly(negative) and that she did worse than her partner in the reporting task. The positive feedback served as the upward comparison, while the negative feedback served as the downward comparison. To measure self esteem, a Rosenberg self esteem scale was given to the students two weeks before the reporting task was given to them. The same Rosenberg self esteem scale was again given to them after the reporting task and the consequent upward and downward comparison feedbacks. The expectation of this study is that lower self esteem will result after an exposure from upward comparison than in downward comparison. A lower self esteem was also expected after comparison with friends than with non friends. No significant differences were found in the self esteem of the subjects after having been subjected to social comparison with their friends or non friends in a reporting task. No significant main effect were found between comaprison with friends and non friends in a reporting task. No significant main effect were found between upward and downward comparisons with others in a reporting task. No significant reaction effects were found between social comparison and friendship. A pitfall in the research design was observed to be responsible for the absence of significant differences in the results of the study. These are attrition of subjects, failure to administer manipulation checks, failure to pre-test most of the instruments, and minimal control in the environment.